Is Information Making Sense in Decisions, And Will Changes in Standard Behavior: Focus Pandemic - Teguh Purnomo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The pandemic period due to COVID-19 resulted in all changes in activities in human-human relations in any activity, be it socio-economic, cultural, or educational (Yuniarto et al., 2021). This study focuses on whether there are changes to new standards of behavior for information on COVID-19 and whether there are changes to new standards of behavior for awareness of COVID-19. This research was a qualitative technique that sampled teachers and students at the early childhood education level using a purposive sample design technique carried out in Srono sub-district. Collecting data using interviews and field observations. The results of the study show that new behavioral changes in awareness of COVID-19 also result in changes in new standards of behavior for awareness of COVID-19. The conclusion of the study shows a good relationship between information, awareness, and behavior formation in response to the covid-19 pandemic.